Profile of occupational accidents reporting to a rural Plantation Hospital: A record review - Naveen, R; Swaroop, N; Agrawal, Suyash; Tirkey, Anup Kumar (International Journal of Occupational Safety and Health, 2014)
Background: Plantation industries in India employ over 1 million people and are among the largest private employers in India. Plantations employ both skilled and un-skilled labour’s. The risks of occupational accidents are higher among this population due to the unfavorable working conditions. Objectives: To study the profile of occupational accidents and to describe the time trend of these occupational accidents. To assess changes if any in the profile of occupational accidents reporting to a rural plantation hospital over the last decade. Methodology: A descriptive hospital record review of all the patients presenting with occupational accident from January 2008 to December 2009. Results: 439 patients were registered with history of accidents; among them 196 were occupational accidents. Majority of the victims of the accident were in the age group of 21 – 40 years and were among males. Most common type and site of injuries were superficial injuries on the upper limbs. There is no significant change in the profile on occupational accidents over the last decade. DOI: http://dx.doi.org/10.3126/ijosh.v3i2.6138